2012
DOI: 10.1016/j.jesf.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training frequency on physiological adaptations in older adults

Abstract: Resistance training is an effective way to achieve optimal gains in muscle mass and strength and has also been well documented in attenuating various forms of skeletal muscle wasting (e.g., sarcopenia). Moreover, it has been demonstrated that with appropriate training, older adults can reverse strength and muscle mass deficits to younger levels. To attain maximal benefits, careful manipulation of training variables, such as intensity, volume and frequency, is required. Although training intensity and training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
6
20
0
2
Order By: Relevance
“…A frequência de treinamento refere-se ao número de sessões realizadas durante um período específico de tempo e também pode ser caracterizada como o número de sessões nas quais um mesmo exercício ou grupamento muscular é exercitado por semana 16 . Alguns estudos já investigaram a influência desta variável sobre as adaptações ao treinamento em populações diversas [16][17][18][19][20][21][22][23][24] ; porém, poucos experimentos analisaram a influência exclusiva do TF sobre o desempenho funcional na população idosa 5,8,9,25 .…”
Section: Introductionunclassified
“…A frequência de treinamento refere-se ao número de sessões realizadas durante um período específico de tempo e também pode ser caracterizada como o número de sessões nas quais um mesmo exercício ou grupamento muscular é exercitado por semana 16 . Alguns estudos já investigaram a influência desta variável sobre as adaptações ao treinamento em populações diversas [16][17][18][19][20][21][22][23][24] ; porém, poucos experimentos analisaram a influência exclusiva do TF sobre o desempenho funcional na população idosa 5,8,9,25 .…”
Section: Introductionunclassified
“…Although Farinatti et al 7 reported that the participants were physically active, none were engaged in a supervised RT program. Thus, it is possible that at least part of the differences found in our study is due to the different levels of previous RT experience of samples from both studies, since Murlasits et al 6 also observed increases in muscle strength in untrained elderly women after eight weeks of a RT program; however, with no differences between weekly frequencies analyzed (2X vs 3X).…”
Section: Discussionmentioning
confidence: 53%
“…Despite using lower intervention period (eight weeks of training) when compared to our study, Gurjão et al 20 observed an even more significant change in SBP (-13 mmHg); however, higher preexperiment BP values may explain, at least in part, the higher magnitude reduction observed 2 . The chronic responses induced by RT are dependent of the volume and intensity manipulation [6][7][8] . Brito et al 8 verified larger-scale reductions in post-exercise BP in trained hypertensive older subjects submitted to higher volume RT protocol (simple sets vs multiple sets).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30][31][32] These studies have had mixed results with some studies showing that 3 days per week of RT is superior to 2 days per week for improving muscular strength and/or physical functioning, 26,28,30,32 whereas other studies have shown no differences. 27,29,31 Regardless, these findings are not likely generalizable to prostate cancer survivors because most previous studies have focused on younger adults 26,27,32 or older women. 28,30 In addition to being older men, prostate cancer survivors experience disease-and treatment-related side effects that may alter their response to different doses of RT.…”
Section: Introductionmentioning
confidence: 99%